2015
DOI: 10.1515/tjb-2015-0033
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organophosphate resistance status and mechanism in Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) from Turkey / Türkiye’deki Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae)’nin organofosfat direnç durumunun ve mekanizmasının belirlenmesi

Abstract: Objective: The objectives of this study were to determine resistance status to malathion and pirimiphos- methyl insecticides and to make biochemical analysis of resistance mechanism(s) developed to these insecticides in Sitophilus zeamais (S. zeamais) populations, collected from two different locations in Turkey. Two organophosphate insecticides, malathion and pirimiphos- methyl, were examined by bioassay using a discriminating dosage technique with impregnated filter papers. Mortality percentages were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Furthermore, Attia et al (2020) found that the Egyptian populations of the rice weevil S. oryzae were 199.6 times resistant to 24 hours of malathion exposure. Karaağaç & Konuş (2015) determined the mortality rates at the dose of 1.5 mg malathion/disc of Sitophilus zeamais Motschulsky, 1855 (Coleoptera: Curculionidae) populations collected from Kırıkkale and Samsun as 72.2 and 92.2%, respectively. They reported that cytochrome P450 monooxygenase and glutathione S-Transferase enzymes may have a role in the resistance against malathion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Attia et al (2020) found that the Egyptian populations of the rice weevil S. oryzae were 199.6 times resistant to 24 hours of malathion exposure. Karaağaç & Konuş (2015) determined the mortality rates at the dose of 1.5 mg malathion/disc of Sitophilus zeamais Motschulsky, 1855 (Coleoptera: Curculionidae) populations collected from Kırıkkale and Samsun as 72.2 and 92.2%, respectively. They reported that cytochrome P450 monooxygenase and glutathione S-Transferase enzymes may have a role in the resistance against malathion.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, while the Ankara population of S. zeamais showed resistance to malathion, no resistance was detected in the Samsun population. They evaluated that cytochrome P450 monooxygenases play an active role in malathion resistance in the Ankara population of S. zeamais (Konuş, 2015). Karaağaç (2015) found that there was no resistance against malathion except for Ankara and Karaman strains of S. zeamais.…”
Section: Discussionmentioning
confidence: 99%